Dual Antiplatelet Therapy Improves Functional Outcome in Patients With Progressive Lacunar Strokes. Issue 4 (April 2019) - Berberich, Anne; Schneider, Christine; Reiff, Tilman; Gumbinger, Christoph; Ringleb, Peter Arthur
Abstract : Background and Purpose—: In 20% to 30% of patients with lacunar strokes, early neurological deterioration (END) occurs within the first days after stroke onset. However, effective treatment strategies are still missing for these patients. The purpose of this study was to analyze efficacy of dual antiplatelet therapy (DAPT) in patients presenting with END. Methods—: Four hundred fifty-eight patients with lacunar strokes and corresponding neuroimaging evidence of lacunar ischemia were retrospectively screened for END, which was defined by deterioration of ≥3 total National Institutes of Health Stroke Scale points, ≥2 National Institutes of Health Stroke Scale points for limb paresis, or documented clinical deterioration within 5 days after admission. Patients with END were treated with DAPT according to in-house standards. Primary efficacy end point was fulfilled if National Institutes of Health Stroke Scale score at discharge improved at least to the score at admission. Secondary end points were Rankin Scale score, further clinical fluctuation, and symptomatic bleeding complications. Results—: END occurred in 130 (28%) of 458 patients with lacunar strokes. Ninety-seven (75%) of these patients were treated with DAPT after END, mostly for 5 days. DAPT was associated with improved functional outcome. The primary end point was met in 68% (66) of patients with DAPT compared with 36% (12) of patients with standard treatment ( P =0.0019). Further clinical fluctuations were absent in 79% (77) of patients with DAPT versus 33% (11) of patients without DAPT ( P <0.001). Symptomatic bleeding complications were not observed in any patient. Conclusions—: The results demonstrated potential positive effects of DAPT in patients with progressive lacunar strokes. Abstract : Supplemental Digital Content is available in the text.